The Sixth general election to Lok Sabha - Shakdher, S. L., 1918- (Published for Lok Sabha Secretariat by Oxford & IBH Pub. Co., 1977)
Comprises chiefly the manifestoes and statistical information of different political parties involved in the 1977 general election of india.